PENGARUH PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN AYAM KQ 5 KOTA MOJOKERTO - Rini Armin (Pro-fit, 2022)
This research was conducted by questionnaire method using accidental sampling technique to 100 consumers who happened to be in Chicken Restaurant KQ 5. Analysis of data obtained in the form of quantitative analysis includes validity and reliability test, test Classical assumption, multiple regression analysis, Goodness of Fit test through F test and t test and regression coefficient analysis (R2). The results of this study indicate that all independent variables together positively affect the consumer satisfaction and also have an individual positive impact on customer satisfaction. Thus, product quality and service quality influence positively and significantly to consumer satisfaction at Rumah Makan Ayam KQ 5 In Mojokerto, where product quality is dominant variable, it can be seen regression coefficient from product quality (X2) equal to 0,127 and tcount 2,859 . Based on the research results suggested Chicken Restaurant KQ 5 In Mojokerto need to pay attention and improve the quality of restaurants to be better, especially on the quality of service variables related to customer satisfaction or customer satisfaction.